Elite structure and the provision of health-promoting public goods - Tommy Krieger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We compile biographical information on more than 5,000 Prussian politicians and exploit newly digitized administrative data to examine whether landowning and landless elites differ in the extent to which they support health infrastructure projects. Using exogenous variation in soil texture, we present results from 2SLS regressions, suggesting that the provision of health-promoting public goods improves with the political influence of the landless elite. We also provide evidence for two mechanisms: first, landless elites face a higher risk of strikes, and second, they have more economic benefits from improving the health of the poor. Finally, we illustrate that the relevance of these two channels differs for those health-related public amenities that improve the access to medical care and those that prevent the outbreak of infectious diseases.
Keywords: H11; H41; H75; I15; N33; O43; P16; 330; biographical data; distribution of power; health; land inequality; landowners; local elites; political power; Prussian history; public good provision; redistribution